Motherhood and competitive coaching: six stories of generational differences in persisting and resisting gender inequities in sport - Trussell, D. E.; Mooradian, J.; Porter, J.; Clutterbuck, R. (Qualitative Research in Sport, Exercise and Health, 2024)
In this paper, we examine mothers` experiences of coaching; specifically investigating the nuances of generational cohorts (i.e. Generation X and Millennials). Using critical feminist narrative inquiry, we conducted interviews with fourteen mother-coaches (apprentice, assistant, or head coaches) within the context of an amateur national, 10-day multi-sport games event in Canada. Participants represented eight different provinces across Canada and 10 different sports. Three themes were constructed that call attention to the Canadian coaching culture: a) creating space in sport`s hetero-patriarchal culture, b) sport policy reproduces gendered coaching discourses, and c) reimagining coaching and the value of communities of practice. The findings draw attention to the importance and variation among generational cohorts and how mother-coaches engage in individual and collective acts of resistance to the everyday inequities. This study highlights the importance of support (e.g. from spouses and other women coaches) while exposing systemic inequities.